PENGAWAS MADRASAH KOTA PAYAKUMBUH DAN PROBLEMATIKANYA - Isra Hayati Darman (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2016)
Supervisor is a functional position of a civil servant in Indonesia whose duty is to execute supervising programs in the field of education both at schools and madrasahs. Meanwhile, supervision is an important program to increase the quality of education. Good supervision can motivate teachers, principals, and other educational staff to improve their profesionalism and work. Lately, Supervising programs at schools become better and professional. The program was an inspecting action in the past, but now it develops to be a guide and training. However, it still has problems that need to solve accurately. The research is aimed at expressing, discussing, and finding a solution to the problems faced by supervisors of madrasah at the Ministry Of Religious Affairs (MORA) of Payakumbuh. The main problem of the research is the quantity of supervisor is not logical if it is compared to the number of madrasahs and teachers. Based on the data at MORA of Payakumbuh, it was obtained the number of supervisors, madrasahs, and teachers as follows; 3 supervisors, 14 madrasahs, and 408 teachers. The illustration above shows that the heaviness of supervisors’ duty in supervising three hundred and twenty-nine madrasah teachers in Payakumbuh. In order to solve the problem, the supervisors with MORA of Payakumbuh conducted programmed supervision through activities of Teachers’ Association (MGMP & KKG) twice a month regularly, and The Madrasah’s Principals Association (MKKM. The activities are funded by MORA of Payakumbuh.